Acinetobacter baumannii pRAY plasmids – An age-old, stealthy vehicle for the transmission of aminoglycoside resistance, overlooked - Yeo, Chew Chieng; Soo, Sum Lean (2017)
This study aimed to evaluate the chemical compositions and DPPH free radical scavenging activity of local lemon myrtle (Backhousia citriodora) leaf extracts. While this is native Australian plant, it is still new in Malaysia and not many research have been conducted on Backhousia citriodora in Malaysia. Lemon myrtle leaf was extracted subsequently with three solvents which were pet ether, ethanol and aqueous. After concentrated under vacuo, all crude extracts obtained were evaluated for total phenolic content, total flavonoid content, total neutral sugar content, DPPH free radical scavenging activity and FTIR profiling. As a result, aqueous extract of local lemon myrtle leaf showed the highest total phenolic and flavonoid contents with respective values was 13.57 mg GAE/g and 13.19 mg QE/g sample compared to other extract. Moreover, ethanol extract of this plant also exhibited the highest antioxidant activity (78.03%). There were strong correlation between antioxidant activity and total phenolic as well as flavonoid content with both correlation values (R2 ) are more than 0.9. Thus, this research can contribute to advancement of food industry and give valuable information for further study on the lemon myrtle of Malaysia.